Strategi Public Relations PT. MNC Sekuritas Dalam Meningkatkan Brand Awareness Melalui Event Investor Gathering - Asmara, Ahmad Agus (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Business in the securities company industry is very competitive, with many competitors offering similar services in Indonesia. This competition encourages securities companies to continue to increase and expand their client base, as well as maintain a good reputation in this industry. So that securities companies can continue to be able to survive amidst this business competition, business people must think hard to provide the best service for investors and partners. work to attract a wide audience. Public Relations is a communication activity carried out with a specific purpose. This is the case with the strategy carried out by PT. MNC Sekuritas with the aim of building Brand Awareness appropriately both in the competition and in the minds of the public. The background to this research was wanting to know the Public Relations strategy of PT. MNC Sekuritas in Increasing Brand Awareness. This research uses a qualitative descriptive method. The results of the research showed that there were achievements from the investor ghatering event. After this activity was held, respondents seen from the company's internal research statistical graphic data, in March there was an increase in potential investors, followers, and views of the motion trade application also increased by 15%. Apart from that, MNC Sekuritas' public relations succeeded in inviting investor ghatering participants to provide education and introduce MNC Sekuritas itself, in increasing Brand Awareness through partnership collaboration, events, communities, brand awareness is very important therefore complete information is very important because it influences the communication process itself .